Love is in the air. Consumers' perception of products from firms signaling their family nature - Natalie Rauschendorfer; Reinhard Prügl; Maximilian Lude (Psychology & Marketing, 2021)
Signaling consumers that the company behind a brand is run by a family is increasingly observable in the marketing realm. One possible reason could be the emotional value signaled by the family nature of the firm. Brand signals carrying emotional value might contribute to a competitive advantage. Since we do not fully understand the effect of signaling the family nature of a firm yet and as family represents an emotional context, we examine this effect on consumer perceptions of the products being made with more love by conducting two experimental studies. In Study 1 (N0.167em=0.167em371) we find that the firm's family nature triggers a strong perception of love being part of the production process of the brand, which leads to a higher willingness to pay. Specifically, in Study 2 (N0.167em=0.167em280) we designed a process manipulation study to provide causative experimental explanation of the process of Study I. Thereby, we contribute to psychology and marketing research by showing that consumers consider a product signaling the family nature of a firm more strongly to be made with love and are willing to pay a price premium. This effect is driven by positive feelings related to one's own family.
Keywords: 650; experimental study; family firm perception; family nature; love; made with love perception; priming; signaling; signaling theory; willingness to pay